2015
DOI: 10.15537/smj.2015.2.10205
|View full text |Cite
|
Sign up to set email alerts
|

Type-B lactic acidosis associated with progressive multiple myeloma

Abstract: We report a 64-year-old lady with stage II, Immunoglobulin-G lambda multiple myeloma (MM) (standard risk), who presented with type-B lactic acidosis (LA), and multi-organ dysfunction associating myeloma progression, and ending in imminent death. In the context of literature review of all previously reported similar cases, this report highlights and discusses the association of type-B LA and MM (especially progressive disease), and also emphasizes the poor outcome. Early recognition of this condition with inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…First, pH of MM cell conditioned media was tested at different time points. We found that 72 h of MM cell culture generate acidic tumor microenvironment close to the pH tumor environment cited in the literature around 6.5-7.1 [27-29]. The pH of the conditioned media was measured after 72 h of culture and found a significant decreased in pH in MM-conditioned media (6.94 ± 0.23) compared to normal PB MNCS-conditioned media (8.38 ± 0.01) and non-conditioned media (8.6 ± 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…First, pH of MM cell conditioned media was tested at different time points. We found that 72 h of MM cell culture generate acidic tumor microenvironment close to the pH tumor environment cited in the literature around 6.5-7.1 [27-29]. The pH of the conditioned media was measured after 72 h of culture and found a significant decreased in pH in MM-conditioned media (6.94 ± 0.23) compared to normal PB MNCS-conditioned media (8.38 ± 0.01) and non-conditioned media (8.6 ± 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…We have previously shown that chitosan swelling (as a first step for drug release) is pH dependent, in which chitosan swelling is increased in acidic pH and enhance release for its encapsulated materials [41], due to hydration of the protonated amine groups under acidic conditions [42]. Tumor microenvironment is reported to be more acidic than normal healthy tissue [27-29], and our model demonstrated similar pH in the MM cultures to these reported in the literature. We further confirm that anti-CD38 NPs swelling was pH dependent, and that acidic tumor microenvironment induced increase swelling compared to normal microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite persistent elevation of lactate, he remained stable and was extubated. He was discharged to ward after 5 days, in much improved condition but with lactate still in range of 5–10 mM, a phenomenon that has been described in patients with multiple myeloma [2830]. He was diagnosed by a posteriori consensus of clinicians as having type B lactic acidosis due to multiple myeloma.…”
Section: Resultsmentioning
confidence: 95%
“…Most reported cases of type B lactic acidosis are associated with hematological malignancies. Multiple case reports have been reported with patients of multiple myeloma, 21 lymphoma, and leukemia 22 complicated by type B lactic acidosis. The data on solid tumors are limited, and we performed literature search using PubMed with the search terms “type B lactic acidosis” and “lactic acidosis and colon cancer.” Our case represents the second case in the literature in the last 20 years, associating colorectal cancer with severe type B lactic acidosis.…”
Section: Discussionmentioning
confidence: 99%